Revealing the hidden geography of alternative food networks: The travelling concept of farmers' markets - Fendrychová, Lenka; Jehlicka, Petr (Pergamon - Elsevier Science, Ltd., 2018)
Alternative food networks in post-socialist settings are often studied using concepts and analytical tools developed in the Anglo-American context. As a result, the findings tend to replicate and confirm rather than challenge and extend the extant knowledge and theorisations. Based on a recent study of farmers' markets in the Czech capital Prague, the paper claims that viewing these 'from the periphery' produces novel insights complementing those garnered in researching them in the West. In the context of earlier alternative food initiatives, the boom of farmers' markets, which Prague experienced in the early 2010s, was unparalleled. In less than 24 months, 41 farmers' markets were established in and around the city. Focusing methodologically on the discourse of the organisers of farmers' markets and theoretically on the complex hidden geography underlying the farmers' markets' boom, we are able to unpick the intricacy and paradoxical nature inherent in this development. While acknowledging the farmers' markets embeddedness in the local context, we argue that a more comprehensive understanding of farmers' markets requires engagement with a flow of ideas and know-how transcending the locality. The ensuing type of farmers' markets is a result of interactions among different travelling concepts as well as of their encounter with the specificities of the local post-socialist context. We argue that the fact that these concepts were not necessarily concordant with each other and also insufficiently adapted to the local context had a profound effect on Prague farmers' markets' boom.
Keywords: Alternative food networks; Farmers' markets; Food relocalization; Post-socialism; Situated knowledge; Travelling concepts